Novel de novo SPAST mutation in a Han Chinese SPG4 patient: a case report - Xu, Yu-Han; Yuan, Bao-Yu; Ji, Jia-Le; Wu, Di; Zhou, Hong; Guo, Yi-Jing (Frontiers in Genetics, 2024)
Spastic paraplegia type 4 (SPG4), the predominant form of Autosomal Dominant Hereditary spastic paraplegia (AD-HSP), is characterized by variants in the SPAST gene. This study reports a unique case of a late-onset SPG4 in a Han Chinese male, manifesting primarily as gait disturbances from lower extremity spasticity. Uncovered through whole-genome sequencing, a previously undocumented frameshift variant, c.1545dupA in exon 14 of the SPAST gene, was identified. Notably, this variant was absent in asymptomatic parents with confirmed paternity and maternity status, suggesting a de novo variant occurrence. This discovery emphasizes the potential of de novo variants to exhibit a late-onset pure pattern, extending the SPG4 variant spectrum, and consideration of such variants should be given in HSP patients with a negative family history.